EVALUASI KESEHATAN BANK BERBASIS RISIKO, TATA KELOLA, PROFITABILITAS, DAN PERMODALAN DALAM KERANGKA RGEC PADA PT BANK NEO COMMERCE TBK TAHUN 2022–2024 - Indri Iswardhani (Jurnal Ilmiah Akuntansi, 2026)
This study aims to evaluate the health level of PT Bank Neo Commerce Tbk (BBYB) for the 2022-2024 period using the Risk-Based Bank Rating (RGEC) approach, which includes four main aspects: Risk Profile, Good Corporate Governance (GCG), Earnings, and Capital. The research method used is descriptive quantitative analysis with secondary data sourced from BBYB's annual financial reports. The results show that during the 2022-2024 period, BBYB experienced a consistent improvement in its health level, reflected in the composite score increasing from 66.67% (PK-3 with "fairly healthy" predicate) in 2022 to 75% (PK-2 with "healthy" predicate) in 2024. This improvement was primarily driven by significant enhancements in the risk profile aspect, particularly the LDR ratio which improved from 93% (fairly healthy) in 2022 to 68% (very healthy) in 2024, while NPL remained stable in the healthy category at 2-3%. The profitability aspect showed improvement with ROA increasing from -5.09% (unhealthy) in 2022 to 0.11% (less healthy) in 2024, while NIM consistently maintained a very healthy predicate above 23%. The capital aspect demonstrated very strong performance with CAR consistently above 27% with a very healthy predicate throughout the research period. However, the GCG aspect experienced a decline from "healthy" predicate in 2022 to "fairly healthy" in 2023-2024. This study emphasizes the importance of strengthening GCG principles implementation and continuously improving profitability to support the future growth of digital banks.